Menganalilis Seberapa Besar Pengaruh Sepinya Konsumen Pasar Tradisional Cimindi Di Kota Cimahi - Iis Nurkamilah; Ageng S.Kanda (STIKes Ibnu Sina Ajibarang, 2024)
Background: Based on observations in the field, researchers see that there are still many kiosks that are not used and traders tend to sell on the ground floor which is close to the main road or which is easily accessible to the public or buyers so that the rest are empty, especially on the 2nd floor where the top roof has not been completed. So far, traders consider that stalls on the lower floors have more customers compared to traders selling on the upper floors, so many traders place their activities outside the Cimindi Market area and become street vendors. This creates complex problems, apart from aesthetic and The decline in the quality of the environment can also cause congestion on the roads around Cimindi Market. .Research method: this research pattern uses a qualitative approach. According to Tanzeh, Qualitative research is research that is intended to reveal symptoms holistically-contextually (thoroughly and in accordance with the context/what is) through collecting data from natural settings as a direct source of the key research instruments themselves.⁶⁵ .Conclusion: Based on the research results regarding